Teacher Beliefs about Growth Mindset in Pre-Service Mathematics Teaching - Lathifah, Hannif; Parnata, Indhiadma; Istiqomah, Fadhilah Nur; Sholekah, Iis; Maghfiroh, Khikmatus Shahrin; Sunaifah, Ivatus; Badriyah, Lailatul; Faradiba, Surya Sari (Jurnal Likhitaprajna, 2026)
This study explores how classroom discourse reflects the implementation of growth mindset principles in mathematics learning by pre-service teachers during their teaching practicum at SMAN 4 Malang. The research focuses on how feedback practices, questioning strategies, and task design support students’ engagement, reasoning, and responses to challenges. A qualitative approach was employed through classroom observations and analysis of instructional interactions conducted by pre-service teachers. The findings reveal that the learning environment demonstrated several key characteristics of a growth mindset-oriented classroom. Pre-service teachers were able to create a supportive atmosphere that encouraged student participation, idea expression, and reasoning. Practices such as promoting student thinking and normalizing mistakes were particularly evident, helping students focus on conceptual understanding rather than merely obtaining correct answers. However, the feedback implementation tended to emphasize correctness rather than students’ effort and strategies, and opportunities for productive struggle were limited due to relatively quick intervention and uneven scaffolding. As a result, students had fewer opportunities to engage in sustained independent problem-solving, which is essential for developing persistence and resilience. Overall, the study highlights the need for more explicit emphasis on effort-based feedback and greater opportunities for students to engage with challenging tasks. These improvements are expected to strengthen students’ growth mindset, persistence, and deeper understanding in mathematics learning. The contribution of this study lies in providing empirical insights into the implementation of growth mindset principles in mathematics teaching practices by pre-service teachers, particularly in terms of classroom discourse. The findings may serve as a basis for reflection and the development of teacher education programs aimed at designing instructional interactions that better support students’ growth mindset development.